2022
DOI: 10.21037/qims-21-435
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent associations between distinct subtypes of childhood trauma and brain function and architecture

Abstract: Background: Childhood trauma can alter brain-development trajectories and lead to a greater risk of psychopathology developing in adulthood. For this reason, understanding experience-dependent brain abnormalities associated with different trauma subtypes is crucial for identifying developmental processes disrupted by unfavorable early environments and for proposing early intervention measures to reduce trauma's negative effects.Methods: This study used multimodal magnetic resonance imaging (MRI) to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…In addition, the NAc and SoM are important brain regions related to symptoms in trauma victims. While NAc hypoactivation is related to atypical reward functioning in individuals with early adversities in childhood and/or adolescence ( Goff et al, 2013 ), the SoM structure and functional changes shown among those who are emotionally abused may be linked to abnormal sensorimotor function and emotional regulation of traumatic events ( Li et al, 2022 ). Through mediation analysis, we suggest that cognitive factors play a critical role in the neural mechanism of evaluating and recognizing emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NAc and SoM are important brain regions related to symptoms in trauma victims. While NAc hypoactivation is related to atypical reward functioning in individuals with early adversities in childhood and/or adolescence ( Goff et al, 2013 ), the SoM structure and functional changes shown among those who are emotionally abused may be linked to abnormal sensorimotor function and emotional regulation of traumatic events ( Li et al, 2022 ). Through mediation analysis, we suggest that cognitive factors play a critical role in the neural mechanism of evaluating and recognizing emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…We also focused on ET as defined by the presence of emotional abuse and neglect, 62 as they are more related to depressive disorders than other trauma types 67 . Furthermore, trauma subtypes seemingly differentially affect different brain regions, 3,68 and therefore, studies that reduce subtype heterogeneity such as ours are important. Thus, this largely homogenous study has the potential to guide and inform future research, where various aspects can be followed up, generating further hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood trauma has the potential to increase the susceptibility of adults to the emergence of mental disorders. This can be attributed to the fact that childhood trauma elicits a sequence of hormonal and physiological alterations during periods of heightened sensitivity or critical stages, ultimately resulting in excessive overstimulation of neurons and subsequent modifications in brain structure and function [1]. Research findings have revealed notable disparities in neuroanatomy and cognition among individuals who experienced abuse during their childhood [7], implying that those with a history of traumatic childhood encounters exhibit considerable impairments in both the structure and function of their brain.…”
Section: The Effects Of Childhood Trauma On Brain Developmentmentioning
confidence: 99%
“…The various forms of childhood adversity might yield unique neurobiological consequences on the brain. [1] the research investigation employed resting-state functional MRI and structural MRI to explore the correlation between childhood trauma, brain function, and architecture in the population of young adults. The primary objective of this study was to discern the cognitive constituents and modifications in brainbehaviour association associated with each category of childhood trauma.…”
Section: The Effects Of Childhood Trauma On Brain Developmentmentioning
confidence: 99%
See 1 more Smart Citation